Pembuatan Video Company Profile Fakultas Teknik Dan Komputer Universitas Harapan Medan Menggunakan Metode Chroma Key - Anisa Nabila Putri; Dodi Siregar; Mufida Khairani (Department of Information Technology, Universitas Timor, Indonesia, 2023)
The development of technology and information is increasingly rapid, it also has an impact on promotional media which increasingly have many ways of promoting goods or services. One of them is making a company profile video for the Faculty of Engineering and Computers Harapan Medan University, which does not yet have a company profile video as a promotional medium. Making a company profile video using the croma key method aims to introduce the institution to the wider community, convey what is on campus 3, Harapan Medan University and explain what rooms and facilities are on campus 3, Harapan Medan University. Therefore, in this study, a company profile video of the Faculty of Engineering and Computers Harapan Medan University will be made using a green screen effect using adobe illustrator, adobe after effects, and adobe premiere based on multimedia in the form of animated characters as the main characters. The method used in this study is the chroma key method because it combines animation with the original video. The results of this study will make it easier to introduce the Faculty of Engineering and Computers Harapan Medan University. By conducting a study using a questionnaire, researchers can get results from a company profile video that has been made for the Faculty of Engineering and Computers.